Sancta Trinitas unus Deus - Ladaria, Luis F. (Alpha omega, 2018)
The author addresses the question of the teaching on the One God in SacredScripture. There is a progression in divine revelation between the two Testaments, but we may ask ourselves whether accepting this fact necessarily means that it is to be interpreted as a succession in the revelation of the divine Persons. The author presents the different forms of the revelation of the One God in each of the Testaments, before concluding that, being the ‘economy’ of salvation, the ever free and gratuitous overflowing of the love that God is in Himself, this revelation attains its highest point in the ‘definition’ of God as love.